Fabrication of an optical grating using high electrostrictive strain polymer as a template - Ha, Jong-Yoon; Jeong, Dae-Yong; Kim, Jin-Sang; Yoon, Seok-Jin (IOP PUBLISHING LTD, 2007)
This study introduces a simple and inexpensive method of fabrication of optical microgratings, by using a P(VDF-TrFE-CFE) (that is, poly(vinylidene fluoride-trifluoroethylene)-chlorofluoroethylene) terpolymer with high electrostrictive strain as a template. When an electric field was applied to the terpolymer, which has a patterned electrode, a grating formed on the surface. Epoxy was poured onto the grating of the terpolymer template and cured to produce an optical grating. A 22% efficiency of the first-order diffraction was achieved by fabricating an epoxy micrograting in which the terpolymer template was 13 mu m thick with electrode/gap/electrode dimensions of 5 mu m/15 mu m/5 mu m.
Keywords: INTEGRATION